Geronimo Stilton. Books 17 & 18 [compact disc, unabridged] - Lobley, Bill (Geronimo Stilton ;, 2009)
Watch your whiskers, Stilton: A mysterious one-eyed rat is trying to steal The Rodent's Gazette from under my nose! My manager came up with a plan to stop him. He arranged for me to appear on a TV quiz show. But if I lose I have to give up my tail!